The Content Feasibility of An English Textbook Entitled “Pathway to English” by Erlangga for Tenth-Grade Students - Iin, Nona Dwi; Nurkhamidah, Neni (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2024)
Textbooks are an indispensable tool within the educational process, serving as a vital resource for providing students with organized and thorough material. They ensure that students gain the fundamentals of language by providing a well-organized curriculum that aligns with learning objectives and standards. Selecting a textbook is essential as it determines the quality of instructional materials and significantly impacts students’ learning outcomes. This present study intends to determine the appropriateness as well as the strengths, weaknesses, and drawbacks of an English textbook entitled “Pathway to English” by Erlangga for tenth-grade students. This study is categorized as content analysis. All units in the textbook are the subject of the study which will be collected using the documentation technique which will be done by reading and classifying them into the categories provided. After that, the data will be analyzed by using a rubric assessment checklist proposed by Badan Standar, Kurikulum, dan Asesmen Pendidikan (BSKAP). The findings indicated that not all the units in the textbook are appropriate and fulfill the criteria proposed by BSKAP. It fulfilled an average of 80% in total which means it belongs to the ‘good’ category. The finding implies that the textbook needs to be improved to encourage students’ academic success and lifelong love of learning